Online Customer Reviews, Online Customer Ratings, Purchasing Decisions - Steven, Steven; Rakhman, Abdullah (Global Research on Economy, Business, Communication, and Information, 2023)
Online shopping is now popular due to the development of Internet technology that enables shoppers to shop anywhere, anytime. However, behind its convenience, some drawbacks can be detrimental for the users, such as the breadth of the market and variants of similar products offered by different online stores that cause more difficult evaluations for many shoppers. In such a situation, shoppers rely on a shortcut mechanism to make purchase decisions, which considers mainly other customers' ratings and reviews. This study aims to investigate that shortcut in Tokopedia. Therefore, the authors recruited judgmentally 120 shoppers as respondents. Data analysis using multiple linear regression reveals that online customer reviews and ratings significantly and positively influence purchase decisions.